1996
DOI: 10.1073/pnas.93.22.12473
|View full text |Cite
|
Sign up to set email alerts
|

Molecular markers reveal that population structure of the human pathogen Candida albicans exhibits both clonality and recombination.

Abstract: The life history of Candida albicans presents an enigma: this species is thought to be exclusively asexual, yet strains show extensive phenotypic variation. To

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

19
177
1
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(199 citation statements)
references
References 36 publications
19
177
1
2
Order By: Relevance
“…Our initial data showing that a decrease in susceptibility and resistance to 5FC were exclusive characteristics of clade I, and the data presented here showing that a mutant allele of the FUR1 gene was dispersed throughout one clade but absent in non-clade I strains, suggest that if mating does occur, it happens only between members of the same clade. These results are consistent with studies suggesting that the population structure of C. albicans is mainly clonal (4,17). The results presented here reinforce previous concerns (18,24) that not all strains, or clades, of C. albicans are equal, and that representative strains should be selected from each of the five C. albicans clades in future studies of drug resistance or phenotypes of clinical relevance.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our initial data showing that a decrease in susceptibility and resistance to 5FC were exclusive characteristics of clade I, and the data presented here showing that a mutant allele of the FUR1 gene was dispersed throughout one clade but absent in non-clade I strains, suggest that if mating does occur, it happens only between members of the same clade. These results are consistent with studies suggesting that the population structure of C. albicans is mainly clonal (4,17). The results presented here reinforce previous concerns (18,24) that not all strains, or clades, of C. albicans are equal, and that representative strains should be selected from each of the five C. albicans clades in future studies of drug resistance or phenotypes of clinical relevance.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, it was demonstrated that 72% of clade I isolates exhibited reduced susceptibility to 5FC (5FC MIC Ն 0.5 g/ml) compared to 2% of non-clade I isolates (18). The fact that clades maintain their integrity side by side in the same geographical locale, combined with the observation that the majority of clade I isolates are less susceptible to 5FC, indicates that while recombination may occur within a clade, it may be a rare event between different clades (18,24), an interpretation consistent with earlier studies indicating that the population structure of C. albicans is primarily clonal (4,17).…”
supporting
confidence: 75%
“…C. albicans has retained a large number of genes required for mating, and the mating process is elaborate. However, the role of mating in C. albicans continues to be a topic of debate, particularly as the population structure of C. albicans is largely clonal, indicating a predominantly asexual mode of reproduction (Graser et al, 1996;Tibayrenc, 1997). Because the existence of an elaborate mating apparatus is difficult to reconcile with the population structure, we felt it necessary to resolve whether nuclear fusion normally occurs when two C. albicans cells mate.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the effect of genetic recombination shuffling alleles, the multilocus genotypes of pathogens undergoing random genetic exchange will typically not match those in fingerprint databases, unless by chance alone. Such considerations are paramount in the medically important fungi where estimates show that 75% are morphologically sexual, and where several of the morphologically asexual species (which include C. immitis and C. posadasii) have been shown to undergo cryptic recombination in nature (3,22,23). Within Coccidioides, the rate of recombination is high enough that in the two populations that have been extensively surveyed for single nucleotide polymorphisms, only three instances of genetically identical isolates have been found (of which two could have occurred by chance alone), and tests consistently confirm the occurrence of panmixia and linkage equilibrium among markers (17,18).…”
Section: Discussionmentioning
confidence: 99%